Analisis Pengenaan Bea Perolehan Hak Atas Tanah Dan Bangunan Dalam Proses Jual Beli Tanah Dan Bangunan Di Kabupaten Kebumen - Adimas Wahyu Widayat (Universitas Islam Indonesia, 2016)
AbstractProblems in this study, first, first, how the collection of the Tax on Acquisition of Land and Building in the process of buying and selling land and buildings in Kebumen? Second, what the obstacles that arise in the collection fees for acquisition of land and buildings, and how the completion of the constraints that arise in the collection of the fees for acquisition of land and buildings in the process of buying and selling land and buildings in Kebumen? This type of research is empirical jurisdiction. The study concluded, first: the first, for collection of the Tax on Acquisition of Land and Building in the process of buying and selling land and buildings in Kebumen conducted den¬gan self-assessment system which gives credence to the taxpayer to compute, calculate, pay their own taxes ter ¬hutang using BPHTB SSPD form obtained by the taxpayer of DPPKAD Kebumen. Second, constraints-constraints that arise in the collection of the Tax on Acquisition of Land and Buildings include a lack of socialization regarding the manner of payment of BPHTB to the community, the level of public awareness is still very limited to the obligation to pay taxes, dishonesty taxpayers to include the value of purchase and sale transactions deed of sale, the shortage of skilled personnel in DPPKAD and the constraints arising from the bank / cash office area.Keywords: Purchase, Land, Buildings, Kebumen.